ANALISIS TINGKAT KETERAMPILAN BERBICARA SISWA KELAS IV PADA MUATAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Ipinda Intan Saliya; Eko Kuntarto; Silvina Noviyanti (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
One important aspect of language skills, especially in an educational context, is the ability to speak, which plays a crucial role in shaping intelligent, critical, and creative generations. The speaking abilities of children greatly influence their success in both school and at home. Observations and interviews have revealed that some students are less active in speaking, often stutter, and speak softly, and their expressions need improvement. This research aims to analyze the level of speaking skills of fourth-grade students in the subject of Indonesian language at SD Negeri 45/I Sridadi, Muaro Bulian Subdistrict. This study is a descriptive quantitative research that utilizes data from speaking skill tests. The research population consists of all fourth-grade students at SD Negeri 45/I Sridadi, totaling 22 students. The sampling method used is a census. The research results indicate that the speaking skills of fourth-grade students at SD Negeri 45/I Sridadi in the subject of Indonesian language fall into the